An Interdisciplinary Approach to Enhancing Student Engagement and Academic Achievement through Interactive Visual Media - Cecep Sobar Rochmat; Rayna Putri Ramadhani (proceedings.icesy, 2026)
This study examined an interdisciplinary approach to enhancing student engagement and academic achievement through the integration of pedagogical strategies, interactive visual media, and educational psychology. The research was conducted in response to low student participation and learning outcomes in an Islamic junior secondary school, where conventional instructional methods had limited active learning. A Classroom Action Research (CAR) design based on Kurt Lewin’s model was employed and implemented in two cycles consisting of planning, action, observation, and reflection. The participants were 24 eighth-grade students. Interactive visual media in the form of pop-up books were utilized to support student-centered instruction and to accommodate diverse learning styles. Data were collected through classroom observations and learning outcome assessments. The findings indicated a substantial improvement in both student engagement and academic achievement. Student engagement increased from 62.50% in the first cycle to 87.50% in the second cycle, while the average learning score improved from 74.67 to 81.33. These results suggested that the integration of interactive visual media within an interdisciplinary instructional design enhanced learner participation, motivation, and conceptual understanding. This study demonstrated that interdisciplinary instructional design promoted inclusive and resilient learning environments, and that interactive visual media supported active learning and offered flexible possibilities for classroom implementation across diverse educational contexts.